Epigenetic modulation enhances immunotherapy for pancreatic ductal adenocarcinoma - Yan Li; Young K Hong; Xingtong Wang; Harshul Pandit; Qianqian Zheng; Youxi Yu; Xiaoju Shi; Yujia Chen; Min Tan; Zachary Pulliam; Neal Bhutiani; Andrew Lin; et al. (Clinical & Translational Immunology, 2022)
Abstract Objectives Pancreatic ductal adenocarcinoma (PDAC) is an aggressive disease with a poor prognosis. PDAC has poor response to immunotherapy because of its unique tumour microenvironment (TME). In an attempt to stimulate immunologically silent pancreatic cancer, we investigated the role of epigenetic therapy in modulating the TME to improve immunogenicity. Methods In vitro human PDAC cell lines MiaPaca2 and S2‐013 were treated with 5μm 3‐Deazaneplanocin A (DZNep, an EZH2 inhibitor) and 5 μm 5‐Azacytidine (5‐AZA, a DNMT1 inhibitor). In vivo orthotopic murine tumour models using both murine PAN02 cells and KPC cells inoculated in immunocompetent C56/BL7 mice were treated with anti‐PD‐L1 combined with DZNep and 5‐AZA. Short hairpin knockdown (KD) of EZH2 and DNMT1 in PAN02 cells for the orthotopic murine tumour model was established to validate the drug treatment (DZNep and 5‐AZA). qRT‐PCR and microarray assays were performed for the evaluation of Th1‐attracting chemokines and cancer‐associated antigen induction. Results Drug treatments induced significant upregulation of gene expressions of Th1‐attracting chemokines, CXCL9 and CXCL10, and the cancer–testis antigens, NY‐ESO‐1, LAGE and SSX‐4 (P < 0.05). In orthotopic tumour models, inoculation of PAN02 cells or KPC cells demonstrated significant tumour regression with corresponding increased apoptosis and infiltration of cytotoxic T lymphocytes in the combination treatment group. In the orthotopic Pan02‐KD model, the anti‐PD‐L1 treatment also caused significant tumour regression. Conclusion We demonstrate that immunotherapy for PDAC can be potentiated with epigenetic therapy by increasing cancer‐associated antigen expression and increased T‐cell trafficking across the immunosuppressive tumour microenvironment via upregulation of the repressed chemokines and increased apoptosis with subsequent tumour regression.